CSC649: Special Topics in Computer Science / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (Universiti Teknologi MARA (UiTM), 2018)
A course on the fundamental concepts in computer science and technologies embedded into computing systems to perform a certain task. The course will cover specialized technology and described in terms of frameworks and problem formulations, standard models, methods, computational tools, algorithms, as well as methodologies to evaluate the system and select optimal models. The topics are presented as a result of technological change or community or student interest, that include a variety of computer-related skills or intensive study in a specific area of computer science and technologies. A product development in the selected application areas will motivate the coursework and material. The design of the product will focus on critical thinking and quality productivity.